Muhammadiyah dalam Percaturan Internasional - Taufik Temarwut (Journal on Education, 2023)
Muhammadiyah since its establishment on 18 November 1912, by KH Ahmad Dahlan, has introduced itself as one of the organizations with the amar ma'ruf nahi mungkar movement, education, health, Islamic progress, and social organization, as the oldest international organization, which laid the foundation of diversity in the national and international sectors. Muhammadiyah's participation in various interfaith dialogues, international community programs aim to inspire all religious social movements. while at the same time correcting the bad image of Islam in the eyes of the international world. Muhammadiyah has also declared itself to be an Islam of tawasuth that does not lean towards the extreme right and left. even Muhammadiyah does not want to be identified with any ideology or group. So that makes this association truly a role model in Islamic practice.